RETRACTED: AUTHENTIC HAPPINESS OF NUN WHO HAVE MUSLIM PARENTS - Riskasari, Windah (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Retraction Notice: Following reports expressed by a third party via emailat psikis@radenfatah.ac.id about the infringements of professional ethical codesand a considered review of the article entitled